ANALISIS MANAJEMEN WAKTU PADA PROYEK KONSTRUKSI GEDUNG PUSKESMAS A DI KABUPATEN LAMONGAN - Andri anto; Nur Azizah Affandy (Fakultas Teknik, Universitas Wiraraja, 2021)
Writing this research aims to determine the ranking or ranking of every aspect of the implementation of time management and the constraints faced in building construction projects in the construction of Puskesmas A in Lamongan District. Data analysis uses mathematical formula index of importance. The results of ranking or ranking of the implementation of the management of the implementation of the construction of Puskesmas A in the Regency of Lamongan are as follows: Method planning method, improper work implementation with a value of 4,294, Supervisory Factors, difficulty in making an alternative schedule for accelerating projects with a value of 4,411, Factor Tool, mobilization slow tools with an interest value of 4,294, Material Factors, slow material delivery with a value of 4,353, Labor Factors, lack of technical and managerial qualifications for the implementation team with an interest value of 4,118, Financial Factors, lack of financial control and supervision with a value of 4,235, and Communication Factors , Lack of communication and coordination of the implementation team with a score of 4.235.